Gimme shelter - Klein, Libby (Mystery author) (Klein, Libby (Mystery author). Layla Virtue mysteries., 2026)
This whip-smart, witty series packs an emotional punch within an engaging mystery as Layla Virtue, a 30-something recovering alcoholic and former cop turned party musician, finds a sideline in solving murders from her new home in a Potomac County trailer park An unforgettable mystery brimming with hilarity and heart for readers of Margot Douaihy, Jane Pek, and Darynda Jones. As the song says, you can't always get what you want. Maybe that's why, instead of fulfilling her youthful dream of being a rock star, Layla Fortune is living in a trailer park while playing third-rate gigs, including a stint at a '70s Abba brunch. Given everything else she's been through lately, she's not complaining (much) about satin ruffles and go-go boots. She has a squad of supportive new BFFs, and she's reclaimed a relationship with her famous rocker dad. His recent diagnosis has brought them even closer: sharing the trailer park's lake house, which he's had remodeled in typically over-the-top style. Layla's dad loves his new community and the feeling seems mutual. So, why is one of them blackmailing him? It's a mystery almost as baffling as the assignment Layla receives from her former Commissioner: look into the brutal murder of a mild-mannered school teacher. Archie Wilkins was bludgeoned with a candelabra, shot up with drugs, and stuffed into a church confessional. Not the kind of outcome expected for a guy reputed to be the world's nicest. Perhaps Archie had secrets. Perhaps everyone does, including Layla's one-time cop colleagues. She's been blaming herself for a deadly ambush that destroyed her career and her peace of mind, but as her new friends help Layla regain her memories, a different picture emerges, and it's one that forces her to question so much that she's taken as truth . . .